Purification and characterisation of dRP-A: a single-stranded DNA binding protein from Drosophila melanogaster. - Marton, R.F.; Thommes, P.; Cotterill, S. (FEBS Letters, 1994)
Replication protein A (RP-A) is an essential single-stranded DNA binding protein (SSB) involved in the initiation and elongation phases of eukaryotic DNA replication. It has the ability to bind single-stranded DNA extremely tightly and possesses a characteristic hetero-trimeric structure. Here we present a method for the purification of RP-A from Drosophila melanogaster embryos. Drosophila RP-A (dRP-A) has subunits of about 66, 31 and 8 kDa, in line with analogues from other species. It binds single-stranded DNA very tightly via the large subunit. The complete protein has at least a 10- to 20-fold preference for single-stranded DNA over double-stranded DNA and it appears that binding is only weakly co-operative. Band shift experiments suggest that it has an approximate site covering the size of 16 nucleotides or less, however, it shows a greater affinity for long oligonucleotides than for short ones. We also demonstrate that dRP-A can stimulate the activity of its homologous DNA polymerase alpha in excess of 20 fold. Analysis of the protein's abundance during embryo development indicates that it varies in a manner akin to other replication proteins.